2020
DOI: 10.1088/1755-1315/453/1/012034
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation on Green Transformation Competitiveness of Oil-gas Resource-based Cities in China

Abstract: The green transformation is an important direction of the transformation of oil-gas resource-based cities. From the three aspects of environmental protection, resource utilization and transformation, a comprehensive evaluation index system for the competitiveness of the green transformation of oil-gas resources-based cities has been established, and the entropy method has been used to determine the index weights and the correlation matrix method to calculate the comprehensive evaluation score. The green transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…It was found that GDE varies greatly among cities, and the number of efficient cities shows a trend of first decreasing and then fluctuating and increasing, which is consistent with the research of [9] for oil-and gas-resource-based cities.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…It was found that GDE varies greatly among cities, and the number of efficient cities shows a trend of first decreasing and then fluctuating and increasing, which is consistent with the research of [9] for oil-and gas-resource-based cities.…”
Section: Discussionsupporting
confidence: 82%
“…Green development efficiency (GDE) as a manifestation of the coordinated and sustainable development of humanity and nature [3] has played an increasingly prominent role in green development [4]. The research objects on green development in the existing literature range widely, including country-level [5], province-level [6][7][8] and city-level objects [9,10]. However, there exists a particular type of city which plays an important role in providing material resources for economic development: the resource-based city.…”
Section: Introductionmentioning
confidence: 99%